Fundamentals of Management in the Teaching of the Beginning Leader of the Development Institution - Mikoliūnienė, Vanda (Acta Paedagogica Vilnensia, 1998)
This article concentrates attention on the qualification of the beginning leaders in the changing education institutions for the search of curriculum. The essence of adaptation of the common Lithuanian-Finnish curriculum for Lithuania is discussed more widely. The care of the article is the disclosing of the Lithuanian-Finnish programme and also presentation of the experimental results about the adaptation of it for Lithuania. The result of the experiment are positive, the merits of this programme are disclosed in the conclusions. This material can add to the modernization of the management profiled lectures and for the teaching of students of practical cycles and the beginning leaders of the development institutions.